Gender Gaps and the Gender Parity Index in Research in a Colombian Region - Isabel Cristina Rivera-Lozada; César Antonio Bonilla-Asalde; Oriana Rivera-Lozada (Social Sciences, 2025)
Given the difficulty of measuring gender gaps in STI research due to access to comparable information, this research aimed to measure the gender gap in research and the Gender Parity Index for the Department of Cauca, Colombia, in the calls for proposals for Minisciences 2013–2021. This approach is unique to date. The goal of the mixed-methods approach was to determine the gender parity index (GPI) and the gender gaps in research in four fundamental aspects: research area, level of training, classification of researchers, and age groups. The results of the measurement were contrasted with the perceptions obtained from a focus group composed of recognized researchers from the region. The triangulation of the information indicates that the gender gaps are high and the GPI is low, whereas the researchers do not perceive the existence of the gaps, a situation that is detected in the field of administrative management and the scarcity of financial resources for research.